Expression of heat shock protein70 in oral submucous fibrosis and oral squamous cell carcinoma: An immunohistochemical study - M Thubashini; N Malathi; L Kannan (Wolters Kluwer Medknow Publications, 2011)
Background: Heat shock proteins are a highly conserved group of protective cellular proteins whose synthesis is increased in response to a variety of environmental or pathophysiological stresses. Heat shock proteins are useful biomarkers for carcinogenesis in tissues and signal the degree of differentiation and the aggressiveness of cancers. Regulation of heat shock protein 70 (HSP70) expression in oral submucous fibrosis is not known much, and the aim of this study was to evaluate HSP70 expression in oral submucous fibrosis and oral squamous cell carcinoma by immunohistochemical method and to understand the role of HSP70 in tumorigenesis. Materials and Methods: Immunohistochemical method was used to detect HSP70 expression in normal oral mucosa, oral submucous fibrosis (n=30) and oral squamous cell carcinoma (n=20). HSP70 immunoreactivity was correlated with histological and clinicopathological features. Results: A significant increase in expression of HSP70 was observed (P<0.000) as the tissue progressed from oral submucous fibrosis towards oral squamous cell carcinoma. Conclusion: HSP70 is synthesized upon stress situations arising in cells of all living organisms. Expression of HSP70 indicates that stress plays an important role as a predisposing factor in oral submucous fibrosis and its subsequent progression to oral squamous cell carcinoma.